EXTERNAL ECONOMIES OF SCALE OF COMPANIES DOING BUSINESS IN CONGRESS AND BUSINESS TOURISM IN THE CZECH REPUBLIC - Elizbar Rodonaia; Lucie Severova; Alexandr Soukup; Roman Svoboda (European Scientific Journal, ESJ, 2014)
The paper deals with firm´s behavior in international markets and analyses of monopolistic firm´s behavior in long run equilibrium using of microeconomic model. The aim of the paper is to describe the behavior of international firms in congress and business tourism using the model of monopolistic competition. The assumption for application of the monopolistic competition model in the international trade area is the idea that trade increases the market size. In the sectors where external economies of scale apply it is valid that both heterogeneity of the goods the country produces and the extent of their production are influenced by the market size. The above mentioned economic results of the congress and business tourism demonstrate validity of the given model regarding behavior of monopolistic firms on international markets with hotel services. While number of guests is stagnant, we see a decrease in implemented prices during growth of average costs per one day of accommodation, all that with extending offer of services (growing number of hotels, respectively increase of bed capacity). On the other hand, however, with higher number of hotel guests, a growth in prices of accommodation was detected in the last period as a result of lower number of hotels, because some of them ceased to exist. Therefore, stays are currently being sold for higher prices (per one night).